The Influence of Salary and Premium on The Performance of Oil Palm Harvesting Employees in Afdeling 2 PT. Citra Agro Kencana - Muhamad Yazid Bustomi; Sayid Abdullah Asseggaf; Jamaluddin; Arief Rahman; Puspita (Politeknik Pertanian Negeri Samarinda, 2025)
Employee performance is an important aspect of achieving optimal productivity for the company. Providing salaries and premiums is one of the factors believed to affect employee performance. This study aims to determine the effect of salary and premium on the performance of oil palm harvesting employees in Afdeling 2 PT Citra Agro Kencana. The research method used is a quantitative approach with multiple linear regression analysis techniques. The sample in this study amounted to 40 respondents taken through the saturated sampling method. Data were collected through questionnaires and interviews, and processed using the SPSS Version 22 application. The results showed that salary partially had a positive and significant effect on employee performance, while premiums had no significant effect on employee performance. However, simultaneously, salary and premiums have a significant effect on the performance of harvesting employees. This study concludes that providing proper and timely salaries can improve employee performance, while the premium system needs to be evaluated to be more transparent and fair in its implementation.